Monitoring framework for paired experiments to assess the changes in the water balance in urban forests and grass-covered plots - Herceg, András (Acta hydrotechnica, 2025)
Understanding the water balance-modifying effects of urban forests is important for mitigating the impacts of climate change and urbanization. We established a paired plot-based hydrological research area in the Botanical Garden of the University of Sopron as part of a Slovenian–Hungarian OTKA project. The research area is designed for a paired plot examination of water balance (interception, transpiration, groundwater dynamics, infiltration, and runoff) with a forested plot and a grass-covered (control) parcel. Since the plots are located in the university's botanical garden, the proximity allows for diverse and frequent data collection and continuous monitoring. Long-term hydrological measurements offer significant opportunities for studying the water balance in forested areas (as is required for assessing the regime). The monitoring results based on only two years as the observational period can illustrate peculiarities and indicate the significant variability that must be captured, along with the factors required when designing such monitoring. The study presents a monitoring framework that provides insights into the complex water dynamics under the black pine canopy and compares the soil moisture and groundwater dynamics between grass and forest plots.
Keywords: borovci; ground water level; interception; nivo podzemne vode; padavine; pine trees; precipitation; prepuščene padavine; prestrezanje; soil moisture; throughfall; urban forest; urbani gozd; vlaga v tleh; vodna bilanca; water balance